Prescribing for older people discharged from the acute sector to residential aged‐care facilities. Issue 10 (October 2014) - Hopcroft, P.; Peel, N. M.; Poudel, A.; Scott, I. A.; Gray, L. C.; Hubbard, R. E.
Abstract For frail older people, admission to hospital is an opportunity to review the indications for specific medications. This research investigates prescribing for 206 older people discharged into residential aged care facilities from 11 acute care hospitals in Australia. Patients had multiple comorbidities (mean 6), high levels of dependency, and were prescribed a mean of 7.2 regular medications at admission to hospital and 8.1 medications on discharge, with hyper‐polypharmacy (≥10 drugs) increasing from 24.3% to 32.5%. Many drugs were preventive medications whose time until benefit was likely to exceed the expected lifespan. In summary, frail patients continue to be exposed to extensive polypharmacy and medications with uncertain risk–benefit ratio.